Mitochondrial dysfunction and increased glycolysis in prodromal and early Parkinson's blood cells - Smith, A; Depp, C; Ryan, B; Johnston, G; Alegre-Abarrategui, J; Evetts, S; Rolinski, M; Baig, F; Ruffmann, C; Simon, A; Hu, M; Wade-Martins, R (John Wiley & Sons, Ltd., 2018)
Background: Although primarily a neurodegenerative process, there is increasing awareness of peripheral disease mechanisms in Parkinson's disease. To investigate disease processes in accessible patient cells, we studied peripheral blood mononuclear cells in recently diagnosed PD patients and rapid eye movement‐sleep behavior disorder patients who have a greatly increased risk of developing PD. We hypothesized that peripheral blood mononuclear cells may recapitulate cellular pathology found in the PD brain and investigated these cells for mitochondrial dysfunction and oxidative stress. Methods: Peripheral blood mononuclear cells were isolated and studied from PD patients, rapid eye movement‐sleep behavior disorder patients and age‐ and sex‐matched control individuals from the well‐characterized Oxford Discovery cohort. All participants underwent thorough clinical assessment. Results: Initial characterization showed that PD patients had elevated levels of CD14 + monocytes and monocytes expressing C‐C motif chemokine receptor 2. Mitochondrial dysfunction and oxidative stress were increased in PD patient peripheral blood mononuclear cells, with elevated levels of mitochondrial reactive oxygen species specifically in patient monocytes. This was combined with reduced levels of the antioxidant superoxide dismutase in blood cells from PD patients and, importantly, also in rapid eye movement‐sleep behavior disorder patients. This mitochondrial dysfunction was associated with a concomitant increase in glycolysis in both PD and rapid eye movement‐sleep behavior disorder patient blood cells independent of glucose uptake or monocyte activation. Conclusion: This work demonstrates functional bioenergetic deficits in PD and rapid eye movement‐sleep behavior disorder patient blood cells during the early stages of human disease. © 2018 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.